The Role of Cross-Cultural Communication to Balance the Generation Gap in Indonesia - Cloudya Sihombing; Alemina Br. Perangin-angin (Journal on Education, 2023)
This study described how Cross-Cultural Communication contributes its influence on accommodating the generation gap to improve a social structure in Indonesia, particularly during the Disruptive Era. In order to bridge the generation gap, cross-cultural communication focuses on the patterns of convergence and divergence of communication behaviors, particularly as they relate to people's goals for social approval, communication efficiency, and identity. This study was conducted at Universitas Sumatera Utara, and the data was analyzed using a descriptive qualitative method, the constructivism paradigm, and coding. The findings indicated that accommodating in cross-cultural communication can improve problem-solving skills, collective decisions, and can resolve generation gap issues to create harmonious interactions. The failure to play a role in passing on information from one generation to the next is usually based on the assumption that the other generation already knows the condition, situation, and meaning behind it without any further discussion or deeper communication. Because of changes in social structure, the university is developing a cross-cultural communication model to address the generation gap in social structure: openness and engagement, for example, through creative furniture arrangement in some classes. The results also show that student-lecturer engagement is more powerful in creating values for a better social condition. People who are willing to build communication rather than assume it will fare better in all aspects of cross-cultural communication.